MIXED HOLMES AND CEREBELLAR TREMOR FOLLOWING RESECTION OF A FOURTH VENTRICULAR MEDULLOBLASTOMA: A CASE REPORT - S, Subagya; Bayuangga, Halwan Fuad; Pradhani, Distya Nugrahening; Vidyanti, Amelia Nur (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Movement disorders following posterior fossa tumor resection are rare complications. Case Report: A 25-year-old male with obstructive hydrocephalus secondary to a fourth ventricular mass initially underwent ventriculoperitoneal shunting. Three months later, he presented with impaired consciousness and focal impaired awareness seizures manifesting as jerking in the left arm. Brain MRI showed a solid cystic extra-axial mass within the fourth ventricle, compressing the pons and cerebellum. He subsequently underwent a suboccipital decompressive craniectomy with transvermian tumor removal. Histopathology confirmed a Desmoplastic/Nodular Medulloblastoma, CNS WHO Grade 4. The post-operative course was complicated by persistent involuntary movements of the left shoulder that were initially considered refractory focal seizures and did not respond to oral antiseizure medications. Discussion: Detailed clinical evaluation revealed that the abnormal movements represented a mixed movement disorder rather than epileptic seizures. The movement in the left shoulder was consistent with Holmes tremor, a rhythmic tremor with a frequency of approximately 6 to 8 Hz, suggesting involvement of the red nucleus and nigrostriatal pathways. In addition, the left arm showed cerebellar intention tremor with dysmetria, which had previously been interpreted as seizure related jerking. This finding indicated disruption of the cerebello thalamo cortical pathway. These hyperkinetic movements improved after treatment with propranolol and topiramate alongside levetiracetam. Conclusion: This case illustrates a rare presentation of mixed Holmes and cerebellar tremors after medulloblastoma resection. Careful clinical evaluation is essential to differentiate these movements from seizures and guide appropriate treatment.